Evaluasi Kebijakan Pemekaran Kecamatan Pada Aspek Pembangunan Di Kecamatan Siniu Kabupaten Parigi Moutong - Srifridayanti, Srifridayanti (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
The purpose of this research is to identify the economic growth of Siniu Sub-district and identify the constraints to the development of the Sub-district after expansion. The method used in this research is to use secondary data analysis and interviews with research informants in the field. The data that can be analyzed using a qualitative descriptive analysis approach, namely describing the state of the object of research according to the data and facts found in the process of expansion of Siniu Subdistrict. Based on the results of the study, it is concluded that the growth of Siniu sub-district has increased since its formation. However, the increase is still relatively small. From the economic aspect, limited human resources are an obstacle for the Siniu Sub-district area to manage natural resources and potentials in the Siniu Sub-district area. From the aspect of public services, namely education and health, it can be concluded that it has not been maximized. This is due to the condition of school facilities and students that are not proportional to the number of educators. Meanwhile, in the health sector, since its formation in 2008 there has been an increase in the number of health facilities. Although relatively small, these health facilities are very useful for the community.